The Mechanism of Knowledge Resource Interaction in Service Innovation Projects from the Perspective of Value Co-Creation Actors - Lei Xu; Xia Liu; Yanhan Sun; Hu Tao (SAGE Open)
Effective knowledge resource interaction is essential for achieving value co-creation in service innovation projects. Service innovation projects involve collaboration among multiple actors, leading to complex knowledge interactions. However, due to a lack of deep understanding of the mechanisms underlying knowledge resource interaction in multi-actor contexts, effective management of these processes have been challenging, resulting in low value co-creation efficiency in such projects. This study employs the grounded theory approach to identify the key factors and their pathways in the knowledge resource interaction process within service innovation projects. The findings indicate that the knowledge resource interaction mechanism can be explained by four elements: market environment, goal alignment, knowledge capability, and organizational context. These four elements collectively drive and regulate the knowledge resource interaction process. Among them, the market environment is the external driving factor for knowledge interaction, goal alignment serves as the direct motivation, knowledge capability is the critical moderating factor, and the organizational context acts as the safeguarding factor. By constructing a theoretical model, this study reveals the mechanisms of the knowledge resource interaction process, providing decision-making references for enhancing the value co-creation efficiency in service innovation projects.